Kolejny przejaw fenomenu kodyfikacji prawa prywatnego międzynarodowego w Ameryce Łacińskiej – urugwajska Ustawa Ogólna o Prawie Prywatnym Międzynarodowym n°19.920 z 17 listopada 2020 r. Zagadnienia wybrane - Twardoch, Paulina; Klyta, Wojciech (Problemy Prawa Prywatnego Międzynarodowego, 2022)
The article deals with the new Uruguayan act on private international law, i.e. the General Act on Private International Law n° 19.920 of the 17th of November 2020. The authors aim to analyse and assess its solutions, especially in the areas of matrimonial property relations, succession and legal entities, taking into account historical and comparative perspectives. The study presents the origins of the Act, its structure, main characteristics and ideas, and essential novelties introduced thereby. As for matrimonial property relations and succession, the authors focus on the question of the applicable law, while as for legal entities, also on the notion of the recognition of their legal personality. Within the comparative remarks, new Uruguayan provisions are explained against the background of Argentinian, Brazilian, Chilean, Colombian, Cuban, Dominican, Panamanian, Paraguayan, Peruvian and Venezuelan rules, as well as international multilateral conventions and European Union regulations.